Adaptation of the Compensatory Stepping Response Following Predictable and Unpredictable Perturbation Training - Hasegawa, Naoya; Tanaka, Shintaro; Mani, Hiroki; Inoue, Takahiro; Wang, Yun; Watanabe, Kazuhiko; Asaka, Tadayoshi (Frontiers in Human Neuroscience, 2021)
Background Effective training of the backward step response could be beneficial to improve postural stability and prevent falls. Unpredicted perturbation-based balance training (PBT), widely known as compensatory-step training, may enhance the fear of falling and the patterns of postural muscle co-contraction. Contrastingly, PBT with predictable direction or both direction and timing would suppress the fear and the co-contraction patterns during training, but the efficacy of predictable PBT for unpredictable perturbations is still unknown. Objective To compare the adaptation effects of compensatory-step training with and without predictable perturbations on backward stepping against unpredictable perturbations. Methods Thirty-three healthy young adults were randomly assigned to one of the following step training groups: Unpredicted, Predicted, and Self-initiated. In training sessions, participants were perturbed to induce a compensatory step with (Predicted group) or without (Unpredicted group) knowledge of the perturbation’s direction or while knowing both the direction and timing of the perturbation (Self-initiated group). In test sessions (pre- and post-training), participants were instructed to recover their postural stability in response to an unpredicted perturbation. The margin of stability (MOS), center of mass (COM) shift, and step characteristics were measured during a backward step in both test and training sessions. Results All three groups showed a significant increase in the step length and velocity in the post-training sessions compared to those in the pre-training sessions. Moreover, in the Unpredicted and Predicted groups, but not in the Self-initiated group, the MOS at step contact was significantly increased following the training session. In addition, the Self-initiated group showed a significant increase in COM shift at 50 ms after slip onset during training compared to the Unpredicted and Predicted groups. Conclusion Unpredicted and predicted PBT improve step characteristics during backward stepping against unpredictable perturbations. Moreover, the unpredictable PBT and PBT with direction-predictable perturbations enhance the feedback postural control reflected as the postural stability at step contact.